One-pot synthesis of porous N-doped hydrochar for atrazine removal from aqueous phase: Co-activation and adsorption mechanisms. (November 2022) - Yan, Shaojuan; Qu, Jianhua; Bi, Fuxuan; Wei, Shuqi; Wang, Siqi; Jiang, Zhao; Wang, Lei; Yu, Hongwen; Zhang, Ying
Graphical abstract: Highlights: Porous hydrochar made from corn straw was synthesized via KOH/melamine co-activation. KHCN preserved the surface pellet structure and exhibited super SBET (1205.82 m 2 /g). KHCN possessed excellent AT uptake (216.5 mg/g) via the multi-mechanism. N-dopants strengthened the effects of hydrogen bonding and π-π EDA. Abstract: KOH-activated N -doped hydrochar (KHCN) was synthesized via co-activation method to eliminate atrazine (AT) in water efficiently. Compared to primitive HC, KHCN had advantages of splendid specific surface area (1205.82 m 2 /g) and developed microsphere structures on the surface. Specially for KHCN, the extra melamine added strengthened and preserved partial structure of polar oxygen-containing groups that were decomposed in the process of pore making. Besides, the estimated uptake amount of AT onto KHCN (216.50 mg/g) was remarkably superior to KHC (114.25 mg/g). KHCN exhibited the pH-dependence for AT removal, and presented excellent uptake capacity at a relatively neutral environment. Notably, the proposed mechanisms for AT removal by KHCN included electrostatic attraction, pore filling, π-π EDA, H-bond as well as hydrophilic effect. Hence, the porous N -doped hydrochar was a kind of adsorbent which was easy to prepare and had the application prospect for AT removal in natural water.